Multicenter Randomized Trial of Methylprednisolone vs. Intravenous Immunoglobulins to Treat the Pediatric Inflammatory Multisystem Syndrome—Temporally Associated With SARS-CoV-2 (PIMS-TS): Protocol of the Swissped RECOVERY Trial - Welzel, Tatjana; Schöbi, Nina; André, Maya C.; Bailey, Douggl G. N.; Blanchard-Rohner, Geraldine; Buettcher, Michael; Grazioli, Serge; Koehler, Henrik; Perez, Marie-Helene; Trück, Johannes; Vanoni, Federica; Zimmermann, Petra; et al. (Frontiers in Pediatrics, 2022)
Introduction In 2020, a new disease entitled Pediatric Inflammatory Multisystem Syndrome temporally associated with COVID-19 (PIMS-TS), or Multisystem Inflammatory Syndrome in Children (MIS-C), emerged, with thousands of children affected globally. There is no available evidence based on randomized controlled trials (RCT) to date on the two most commonly used immunomodulatory treatments, intravenous immunoglobulins (IVIG) and corticosteroids. Therefore, the Swissped RECOVERY trial was conducted to assess whether intravenous (IV) methylprednisolone shortens hospital length of stay compared with IVIG. Methods and Analysis Swissped RECOVERY is an ongoing investigator-initiated, open-label, multicenter two-arm RCT in children and adolescents <18 years hospitalized with a diagnosis of PIMS-TS. The trial is recruiting at 10 sites across Switzerland. Patients diagnosed with PIMS-TS are randomized 1:1 to methylprednisolone IV (10 mg/kg/day for 3 days) or IVIG (2 g/kg as a single dose). The primary outcome is hospital length of stay censored at day 28, death, or discharge (whichever is first). The target total sample size is 80 patients 1:1 randomized to each study arm. Ancillary and exploratory studies on inflammation, vaccination acceptance and coverage, long-term outcomes, and healthcare costs are pre-planned. Significance Currently, robust trial evidence for the treatment of PIMS-TS is lacking, with a controversy surrounding the use of corticosteroids vs. IVIG. This trial will provide evidence for the effectiveness and safety of these two treatments. Ethics and Dissemination The study protocol, which was designed based on the U.K. RECOVERY trial, the patient information and consent forms, and other study-specific study documents were approved by the local ethics committees (Project ID: 2021-00362). Registration Details The study is registered on the Swiss National Clinical Trials Portal (SNCTP000004720) and Clinicaltrials.gov (NCT 04826588).